2021
DOI: 10.1055/s-0041-1729559
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Clinical Characteristics of Metabolic Bone Disease of Prematurity

Abstract: Objective The study aimed to analyze the risk factors and clinical features of metabolic bone disease of prematurity (MBDP) in premature infants compared with infants of similar gestational age and birthweight without MBDP. Study Design This retrospective case–control study was performed by comparing 81 cases of MBDP with 63 controls to identify potential risk factors. Premature infants with a gestational age ≤33 weeks and birthweight <1,500 g were included. Medical records were examined in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A total of 467 documents were obtained from the preliminary search. According to the inclusion and exclusion criteria, 15 articles were finally included [ 9 – 23 ], including 5 Chinese articles [ 9 – 13 ] and 8 English articles [ 14 19 , 22 , 23 ], 2 Spanish article [ 20 , 21 ]. The literature screening process and results are shown in Fig 1 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 467 documents were obtained from the preliminary search. According to the inclusion and exclusion criteria, 15 articles were finally included [ 9 – 23 ], including 5 Chinese articles [ 9 – 13 ] and 8 English articles [ 14 19 , 22 , 23 ], 2 Spanish article [ 20 , 21 ]. The literature screening process and results are shown in Fig 1 .…”
Section: Resultsmentioning
confidence: 99%
“… 8 , 9 In addition, the late onset of clinical symptoms and signs combined with the lack of specific biochemical markers make early recognition of MBD challenging. 3 , 10 Although numerous epidemiologic studies 7 , 11 , 12 , 13 have identified several risk factors for MBD during the neonatal period, little work has evaluated the prediction of their development. In addition, traditional risk prediction models are limited in forecasting the probability of an outcome, 14 especially a multifactorial disease with a context of large, high-dimensional, and imbalanced data set.…”
Section: Introductionmentioning
confidence: 99%
“…MBD mostly occurs 10-16 weeks after birth [3]. In the short term, bone loss can lead to prolonged hospital stay, ventilator dependence, pathological fractures, which are an important type of fractures in infants within 6 months of birth, and short stature [7][8][9]. In clinical work, insu cient early identi cation of MBD in premature infants may delay treatment and lead to serious consequences.…”
Section: Introductionmentioning
confidence: 99%